Oligomeric interface modifiers in hybrid polymer solar cell prototypes investigated by fluorescence voltage spectroscopy1. Issue 16 (28th April 2015) - Reeja-Jayan, B.; Koen, Katherine A.; Ono, Robert J.; Vanden Bout, David A.; Bielawski, Christopher W.; Manthiram, Arumugam
<x xml:space="preserve">Abstract</x> Exploring the role of oligothiophenes as interface modifiers for TiO2 using fluorescence voltage spectroscopy.